RANCANG BANGUN APLIKASI SISTEM PAKAR UNTUK DIAGNOSIS KERUSAKAN SEPEDA MOTOR MATIC MENGGUNAKAN METODE FORWARD CHAINING - Radia Afnur; Titi Sriwahyuni; Ahmaddul Hadi (Universitas Negeri Padang, 2017)
Improvement of welfare and community mobility services in the economic movementof a country or region, can not be separated from the influence of the development offacilities and infrastructure support such as transportation. One of the most commonlyselected by society ground transportation is motorcycle. The limited knowledge of the ownerabout damage of automatic motorcycle, it happens because of lack of access to earlyinformation, to attempt repairs if there is damage to the motorcycle. therefore, needed asolution for users in studying the damage to the motor and the existence of a motor damageand determine what types damage to the motor with the help of expert system usesadvanced trace inference method (forward Chaining). This application is a web-baseddisplay using the programming language PHP CodeIgniter Framework by using SublimeText 3 Editor and MySQL as the database. Damage to parts of the engine occurred due tonegligence in performing maintenance. Car owners need a periodic maintenance bydetecting any damage that occurs on the motor. Motorcycle owners should receiveinformation early or early diagnosis and identify the components, the characteristics of motorbreakdown as well as solutions to overcome such defects. This is done so that maintenanceand repairs are done right on target, so as to minimize damage to the motor. This applicationis expected to help the owner of the motor to determine the initial diagnosis of the type ofdamage the motor by way of answering the questions about the characteristics of motordamage in the application.Keywords: Matic, Diagnosis, Expert system, forward chaining.